Komunikasi Visual dalam Merepresentasikan Citra Diri Difabel di TikTok pada Akun @Jennifernatalie_ (Perspektif Charles Sanders Peirce) - Nurlailin, Nurlailin (Icon: Islamic Communication and Contemporary Media Studies, 2024)
Social media, such as TikTok, has become the main stage for visual communication for millennials. Apart from normal users, people with disabilities are also active on TikTok, becoming influencers who share their stories, creativity, and experiences with many followers. The author wants to research how people with disabilities express themselves through visual communication on TikTok and how they introduce themselves on social media. focus of the problem in this research is 1). What form of visual communication do disabled people use on the TikTok account @Jennifernatalie_? 2). Charles Sanders Peirce's self-image analysis in @Jennifernatalie's TikTok appearance. Based on the research focus above, this research aims to find out the form of visual communication carried out by disabled people on the TikTok account @jennifernatalie_, and to find out Charles Sanders Peirce's analysis of self-image on the TikTok @Jennifernatalie display. Qualitative methods are used in research and use types of literature or library research, to collect data and information from various sources. Data collection techniques use observation and interviews. Meanwhile, to analyze the data using the theory of Charles Sanders Peirce to determine the form of communication and self-image displayed by @Jennifernatalie_. The results of this research show that there are several forms of visual communication displayed, namely: deaf grab deaf driver content, Joshua prayer, bisindo cover, #trending, motivation, mom and son 25 videos, POV, educational content or stories, and content. sign language 16 videos. Meanwhile, Jennifer Natali's self-image is: patient, full of affection, friendly, and has a warm, harmonious family. Has sincere children, and is tied to his identity as a deaf disabled person.friendly, and has a warm, harmonious family. Has sincere children, and is tied to his identity as a deaf disabled person.